The Cham Rebellion - Jay Willoughby (International Institute of Islamic Thought, 2007)
This book is a study of what happened to Cambodia’s Cham Muslims living in the Khmer Rouge-controlled Kroch Chhmar district (Kampong Cham province) during the 1970s. Based on reconstructed events and survivors’ memories, it is an account of ordinary Muslims caught up in a utopian maelstrom of deceit, brutality, fear, unexpected compassion, torture, and deliberate murder on an almost unbelievable scale while the Muslim world, and the world at large, was “occupied” with other concerns. Chapters 1 and 2 explain how the Khmer Rouge entered the district and found young Cham and Khmer men eager to join up. How could they resist, when Norodom Sihanouk, who enjoyed near-divine status among the peasantry and presented himself as the sole architect of Cambodia’s independence, called upon them to join with the Khmer Rouge (which he had already done) to reverse General Lon Nol’s overthrow of his government? In the “liberated” zones, the Khmer Rouge renamed villages with numbers; selected new Cham village heads based on their lack of education, total servility, and unquestioning obedience; and gradually communalized life because, they promised, that would make the people’s lives better and easier ...